4D Digital Integration for Nanomaterial-Based Monitoring and Treatment of Bridge Piers Defects - Albaqawy, Ghazy Abdullah; Touahmia, Mabrouk; Boukendakdji, Mustapha; Ouazir, Abderrahmane; Mansour, Abdulaziz; Sallam, Ahmed; Sedek, Mohamed Saleh (Buildings (Basel), 2025)
This study presents an innovative 4D digital model that integrates Bridge Information Modeling (BrIM) with several types of data to defect detection in complex bridge structures. The model promotes precise data preparation, navigation, visualization, integration, and monitoring, enabling the identification of defects, like material deterioration, condition changes, and structural clashes in components like trusses. Bridge model provides time-based access to maps, allowing users to explore changes over time and predict future conditions. The integration of time dimension into the 4D model provides dynamic tools for exploring changes over time, allowing for analysis and maintenance planning. Through the use of advanced 4D simulation technology, the study’s effectiveness is in visualizing workflows, identifying constraints, and supporting proactive decision-making in structural management. By incorporating various perspectives and enabling users to interact with detailed visualizations, the model enhances understanding and maintenance practices. This approach advances defect modeling and digitization, supporting automation in defect detection while significantly contributing to the long-term safety and sustainability of bridges. In order to obtain non-destructive images and films of the morphology of the sandstone’s internal structure at the bridge pier in addition to the stone’s grain texture and surface characteristics, this research applied X-ray computed tomography approach (CT scan) and XRF as NDT to the analysis of sandstone.